Implementasi Gagasan Rahmah El Yunusiyah terhadap Pengembangan Lembaga Pendidikan dan Dakwah Islam Muslimat Fatayat Bentayan Tungkal Ilir - Meli Puspita; Rahayu Suprapti; Muhamad Fauzi; Abu Mansur (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2026)
This research explores the implementation of Rahmah El Yunusiyah's ideas in the development of Islamic educational institutions and da'wah at Muslimat Fatayat Bentayan Tungkal Ilir. The research background is based on Rahmah El Yunusiyah's significant contribution to the history of Islamic education in Indonesia through the establishment of Madrasah Diniyyah Putri in 1923, which emphasized holistic integration of Islamic knowledge, general knowledge, character formation, and spiritual development. This research employs a qualitative descriptive method with a field research approach to examine the implementation of principles of equality, independence, and knowledge integration within the institutional context. The research population includes core administrators and active members of Muslimat Fatayat Bentayan, with samples selected using purposive sampling based on competence and involvement in educational and da'wah activities. Data collection was conducted through participatory observation, in-depth interviews, and documentation with data analysis using data reduction, data presentation, and conclusion drawing. Research findings demonstrate that Rahmah El Yunusiyah's ideas are significantly implemented in institutional development through women's leadership training programs, sakinah family development, contextual Islamic education, and Islamic values-based economic empowerment. In conclusion, Rahmah's holistic education principles have been successfully translated into practical guidance for developing inclusive, humanistic Islamic educational and da'wah institutions oriented toward women's empowerment at the local level.